+0  
 
0
55
1
avatar

Let f(x) = 3x + 4 and g(x) = 2x + 8. If h(x) = f(g(x)) , then what is the inverse of h(x)?

 Jul 28, 2021
 #1
avatar+7 
+1

Let us simplify h(x) first. Plugging in the value of g(x) directly into h(x), we get:

 

h(x) = f(2x + 8)

 

We then can plug in 2x + 8 into f(x), to get:

 

h(x) = 3(2x + 8) + 4

h(x) = 6x + 28

 

In order to find the inverse of a function, we have to switch the x and y values first. Hence, we get:

 

y = 6x + 28

x = 6y + 28

 

We then have to solve for y. Solving for y, we get:

 

x - 28 = 6y

(x-28)/6 = y

 

Therefore, the inverse function of h(x) is \(h^{-1}(x) = \frac{x-28}{6}\)

 Jul 28, 2021

30 Online Users

avatar